Molecular characteristics and potential antigenic epitope analysis of porcine epidemic diarrhea virus in China from 2022 to 2025 - Wang, Zunbao; Yang, Kai; Bi, Mingfang; Li, Kaijie; Wang, Wen; Song, Yan; Pan, Xiaomei; Li, Tianzeng; Mo, Xiaobing (Frontiers in Veterinary Science, 2025)
Porcine epidemic diarrhea virus (PEDV) causes varying degrees of diarrhea, vomiting, dehydration, and emaciation in pigs, and severe cases can result in the death of suckling piglets. PEDV is one of the significant viruses affecting the global swine industry. In this study, we investigated the prevalence of PEDV infection in 2,346 pig samples collected from 20 provinces in China, with an overall positive rate of 43.3% (1,015/2,346). Phylogenetic analysis of 15 newly sequenced PEDV strains revealed that 1 strain belonged to the G1c (S-INDEL) genotype, 4 strains to G2b, and the remaining 10 strains to G2c, indicating that G2c is currently the dominant subtype. Compared with the classical CV777 strain, the nucleotide and amino acid sequence identities of the S gene of these 15 PEDV strains ranged from 92.71 to 94.83% and 92.89 to 94.99%, respectively. Amino acid alignment identified mutations of varying degrees within key neutralizing epitopes, including COE, SS2, SS6, and 2C10. Using the server, a new potential N-glycosylation site at position 302 (NKTI) in the S protein of the PEDV/XinJiang/2 strain was identified. Furthermore, linear and discontinuous antigenic epitopes of resolved PEDV proteins were predicted using ElliPro, revealing conserved potential antigenic regions at amino acid 31–54, 90–103, 1,170–1,177, 1,179–1,197, 1,201–1,211, 1,221–1,236, and 1,243–1,254. These findings provide new epidemiological data on PEDV circulating in China and offer valuable insights for the development of future vaccines and molecular diagnostics based on these antigenic epitopes, thereby contributing to improved PED control strategies.